The Potential for Airborne Transmission of SARS-CoV-2 in Sport: A Cricket Case Study - England, Rory; Peirce, Nicholas; Wedatilake, Thamindu; Torresi, Joseph; Kemp, Simon; Cook, Malcolm; Mitchell, Sean; Harland, Andy (International Journal of Sports Medicine, 2021)
A review of risk factors affecting airborne transmission of SARS-CoV-2 was synthesised into an ‘easy-to-apply’ visual framework. Using this framework, video footage from two cricket matches were visually analysed, one pre-COVID-19 pandemic and one ‘COVID-19 aware’ game in early 2020. The number of opportunities for one participant to be exposed to biological secretions belonging to another participant was recorded as an exposure, as was the estimated severity of exposure as defined from literature. Events were rated based upon distance between subjects, relative orientation of the subjects, droplet generating activity performed (e. g., talking) and event duration. In analysis we reviewed each risk category independently and the compound effect of an exposure i. e., the product of the scores across all categories. With the application of generic, non-cricket specific, social distancing recommendations and general COVID-19 awareness, the number of exposures per 100 balls was reduced by 70%. More impressive was the decrease in the most severe compound ratings (those with two or more categories scored with the highest severity) which was 98% and the reduction in exposures with a proximity <1 m, 96%. Analysis of the factors effecting transmission risk indicated that cricket was likely to present a low risk, although this conclusion was somewhat arbitrary omitting a comparison with a non-cricketing activity.
Keywords: COVID-19; coronavirus; sport; risk of airborne transmission; risk factors